Clinical comparison of short and conventional implants placed in the posterior region of the mandible. A pilot study - IBELLI,Guilherme Siqueira (2017)
Abstract Objective To evaluate and correlate the values of radiographic bone density, peri-implant bone height and resonance frequency analysis (RFA) of short or conventional implants placed in the posterior region of the mandible after installing a prosthesis. Material and method Eleven patients were selected for this prospective parallel pilot study. The prostheses were supported by two types of implants: short implants (n = 18) (5.0 x 5.5 mm and 5.0 x 7.0 mm) and conventional implants (n = 23) (4.0 x10 mm and 4.0 x 11.5 mm). The implants were evaluated by RFA, by measuring the bone height, and peri-implant bone density. The implants were evaluated at the periods T0 (immediately after installation of the prosthesis), T1 (after 90 days), and T2 (after 180 days). Result There were no statistically significant differences between groups with respect to radiographic bone density (152.50 ± 15.39 vs. 157.60 ± 28.46, for conventional and short implants, respectively at T2), stability of the implants (Conventional implants: 66.76 ± 10.39 at T0, and 61.85 ± 8.38 at T2 vs. Short implants: 57.50 ± 12.17 at T0, and 61.53 ± 7.39 at T2) and peri-implant bone loss (0.03 mm vs.-0.17 mm, for conventional and short implants, respectively at T2). Additionally, a significant correlation between the evaluated parameters was not detected. Conclusion The short and conventional implants presented similar stability, bone level and density after the activation of occlusion loading.